Hybridisasi Dakwah Pesisir Berbasis Digital-Kultural dalam Penguatan Moderasi Beragama di Kecamatan Bancar Tuban - Siti Kris Fitriana Wahyu Lestari Nana; Auliya Urokhim; Fajar Iriandi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2026)
This study is motivated by the challenges of religious outreach in coastal communities, particularly in Bancar District, Tuban, which faces digital disruption, shifts in patterns of religious communication, and the growing potential for polarization of religious understanding in cyberspace. Problems in da’wah communication arise when traditional da’wah approaches fail to adapt to the development of digital media, while digital religious content often lacks the context of local wisdom among coastal communities. This study aims to formulate a model of digital-cultural hybrid da’wah for coastal communities to strengthen religious moderation among maritime communities in Bancar Subdistrict. The method used is a qualitative approach with a field study design. Data collection was conducted through observation, in-depth interviews with religious leaders, majelis taklim administrators, traditional leaders, and coastal communities, as well as documentation of digital da’wah activities in the Bancar region. Data was obtained from 10 informants consisting of 3 local da’is, 1 mosque administrator, 1 traditional leader, and 5 active congregants. The research findings indicate that the hybridization of coastal da’wah is realized through the integration of social media, visual-educational content, and digital platforms with narratives rooted in local traditions, maritime culture, and the values of Ahlussunnah wal Jama’ah as part of a digital-cultural approach. The resulting model encompasses three main components: adaptive digitalization, cultural reinterpretation, and the internalization of moderation. This approach strengthens inclusive, dialogic, and contextual da’wah communication, thereby contributing to increased tolerance, anti-violence attitudes, and national commitment among coastal communities in Bancar Subdistrict. This study concludes that the hybridization of da’wah based on the integration of digital technology and local wisdom holds strategic potential in strengthening a moderate da’wah ecosystem rooted in coastal communities. The contribution of this research lies in the formulation of a conceptual model for the hybridization of coastal da’wah as an innovative approach to strengthening religious moderation in maritime regions, particularly in Bancar Subdistrict, Tuban